Holism in Ancient Medicine and Its Reception - Thumiger, Chiara (Studies in Ancient Medicine Ser, 2020)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Notes on Contributors -- Introduction -- Part 1 Holism: Methodological and Theoretical Perspectives -- Chapter 1 Holism, Parts, Wholes -- Chapter 2 Holism, Sympathy, and the Living Being in Ancient Greek Medicine and Philosophy -- Chapter 3 'Holism' in Cognitive Approaches to the Ancient Emotions -- Part 2 Is Graeco-Roman Medicine Holistic? -- Chapter 4 Hippocratic Holisms -- Chapter 5 Holism and the Methodists -- Chapter 6 Is Graeco-Roman Medicine Holistic? Galen and Ancient Medical-Philosophical Debates -- Chapter 7 Holism of Body and Mind in Hippocratic Medicine and Greek Tragedy -- Chapter 8 Plato's Charmides on Philosophy as Holistic Medical Practice -- Chapter 9 A Woman in Flux: Fluidity in Hippocratic Gynaecology -- Chapter 10 Cohesive Causes in Ancient Greek Philosophy and Medicine -- Chapter 11 Pneuma as a Holistic Concept in Galen -- Part 3 Medical Holism beyond the Graeco-Roman World -- Chapter 12 Humoralism in Āyurvedic Medicine -- Chapter 13 A Systemic Etiology of Sicknesses from Ancient Iraq: Organ Systems and the Functional Holism of the Babylonian Body -- Chapter 14 Epidemic Disease in a Humoral Environment: From Airs, Waters and Places to the Renaissance -- Chapter 15 Mind-Body Interaction: The Influence of Ancient Ideas in Twelfth-Century England -- Chapter 16 'Treating the Patient, Not Just the Disease': Reading Ancient Medicine in Modern Holistic Medicine -- Index Rerum -- Index Locorum -- Index Verborum (selected).